Advanced dynamic-system simulation model replication and Monte Carlo studies - Korn, Granino A. (Granino Arthur), 1922-; ebrary, Inc. (Hoboken, N.J. : John Wiley & Sons Inc., 2013)
"This book introduces Dynamic-system Simulation with a main emphasis on OPEN DESIRE and DESIRE software. The book includes eight comprehensive chapters amounting to approximately 250 pages, as well as includes three appendices housing information on Radial-basis-function, Fuzzy-basis-function Networks, and CLEARN Algorithm. In addition, a CD will be packaged with each book, containing complete binary OPEN DESIRE modeling/simulation program packages for personal-computer LINUX and MS Windows, DESIRE examples, source code and a comprehensive, indexed reference manual. The second edition offers a complete update of all material, boasting two completely new chapters on fast simulation of neural networks"--
Includes bibliographical references and index.
Electronic reproduction.
Keywords: System analysis -- Simulation methods; Open source software; Computer software -- Development; Electronic books